2018
DOI: 10.1002/hep4.1258
|View full text |Cite
|
Sign up to set email alerts
|

Multitarget Direct‐Acting Antiviral Therapy Is Associated With Superior Immunologic Recovery in Patients Coinfected With Human Immunodeficiency Virus and Hepatitis C Virus

Abstract: Patients coinfected with human immunodeficiency virus (HIV) and hepatitis C virus (HCV) have higher levels of immune activation, impaired antigen‐specific responses, and accelerated fibrogenesis compared to patients monoinfected with HCV. Whether different direct‐acting antiviral (DAA) combinations have differential effects on immunophenotypes and functions following successful HCV therapy remain unknown. Therefore, we aimed to assess the peripheral T‐cell immunophenotypes and functions in patients coinfected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
25
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 43 publications
2
25
0
1
Order By: Relevance
“…28 Additionally, reversal of cirrhosis after SVR seems to be a slow process and the alterations of the immune system may persist after achieving SVR, particularly in cirrhotic patients. 20 Previous studies have described a significant decrease, after SVR with HCV therapy, in peripheral memory T-cells 29 and immune activation (CD4 + CD38 + and CD8 + CD38 + ), [29][30][31] and in plasma levels of biomarkers related to inflammation (interleukin (IL) −6, IFN-γ -inducible protein 10 (IP-10)), 32 bacterial translocation (lipopolysaccharide binding protein, soluble CD14 (sCD14) and fatty acid-binding protein 2 (FABP2)), 30 , 32 and endothelial dysfunction (soluble tumor necrosis factor receptor-1 (sTNF-R1), soluble intercellular adhesion molecule 1 (sICAM-1) and soluble vascular cell adhesion molecule 1 (sVCAM-1)). [33][34][35] However, in the articles there is a lack of consistency in the analyzed biomarkers and the significant biomarkers detected, the timepoints that were used to take the samples after the end of treatment, and the statistical tests used.…”
Section: Introductionmentioning
confidence: 98%
“…28 Additionally, reversal of cirrhosis after SVR seems to be a slow process and the alterations of the immune system may persist after achieving SVR, particularly in cirrhotic patients. 20 Previous studies have described a significant decrease, after SVR with HCV therapy, in peripheral memory T-cells 29 and immune activation (CD4 + CD38 + and CD8 + CD38 + ), [29][30][31] and in plasma levels of biomarkers related to inflammation (interleukin (IL) −6, IFN-γ -inducible protein 10 (IP-10)), 32 bacterial translocation (lipopolysaccharide binding protein, soluble CD14 (sCD14) and fatty acid-binding protein 2 (FABP2)), 30 , 32 and endothelial dysfunction (soluble tumor necrosis factor receptor-1 (sTNF-R1), soluble intercellular adhesion molecule 1 (sICAM-1) and soluble vascular cell adhesion molecule 1 (sVCAM-1)). [33][34][35] However, in the articles there is a lack of consistency in the analyzed biomarkers and the significant biomarkers detected, the timepoints that were used to take the samples after the end of treatment, and the statistical tests used.…”
Section: Introductionmentioning
confidence: 98%
“…In patients with chronic HCV infection, T cell responses can only be detected at low levels [64]. This is because sustained antigenic stimulation results in up-regulation of T cell depletion markers, such as programmed cell death protein 1 (PD-1), programmed death-ligand 1 (PD-L1), T-cell immunoglobulin and mucin-domain containing-3 (Tim-3),cytotoxic T lymphocyte antigen 4(CTLA-4),CD160, B-and T-lymphocyte attenuator [65], which indicates the increasing population of phenotype of depleted T cells. Ultimately, the outcome of changes in the expression of these genes is that, partial or total loss of antiviral function and proliferation of T cells.…”
Section: Rehabilitation Of Immune Damagementioning
confidence: 99%
“…Additionally, it is well documented that patients co-infected with HIV and HCV have higher levels of immune activation and impaired antigen-specific responses compared to patients mono-infected with HCV [65].It is important to assess the impact of DAA therapies on recovery of immune dysfunction in subjects with HIV/HCV co-infection. Several small studies have demonstrated improvement in liver ISG expression, restoration of type I IFN signaling, and natural killer and T cell function following IFN-free DAA therapy in the setting of chronic infection [73][74][75].Furthermore, DAA combination therapies in patients co-infected with HIV/HCV resulted in similar restoration of the T-cell impairments and perturbations associated with HIV/HCV coinfection to an extent.…”
Section: Rehabilitation Of Immune Damagementioning
confidence: 99%
See 1 more Smart Citation
“…This is also an excellent model system to study basic immunology questions such as plasticity of the immune system and epigenetic regulation of immune responses in chronic infections and their reversibility. Our group has conducted pioneer clinical trials of DAA for HCV cure [ 2 , 3 , 4 , 5 , 6 , 7 , 8 ] and we investigate immune dysfunction in chronic HCV (CHC) and its recovery in cured individuals [ 9 , 10 , 11 , 12 , 13 , 14 ]. This focused review provides current understanding of innate and adaptive lymphocytes perturbations in CHC patients, the status of these immune cells after viral clearance with DAA, and implications thereof (summarized in Table 1 and in Figure 1 ).…”
Section: Introductionmentioning
confidence: 99%